Asymmetric Manipulation of Perpendicular Exchange Bias and Programmable Spin Logical Cells by Spin–Orbit Torque in a Ferromagnet/Antiferromagnet System - Lei Guo; Guopeng Shi; Guocai Wang; Hua Su; Huaiwu Zhang; Xiaoli Tang (Advanced Science, 2024)
Abstract Antiferromagnets are competitive candidates for the next generation of spintronic devices owing to their superiority in small‐scale and low‐power‐consumption devices. The electrical manipulation of the magnetization and exchange bias (EB) driven by spin‐orbit torque (SOT) in ferromagnetic (FM)/antiferromagnetic (AFM) systems has become focused in spintronics. Here, the realization of a large perpendicular EB field in Co/IrMn and the effective manipulation of the magnetic moments of the magnetic Co layer and EB field by SOT in Pt/Co/IrMn system is reported. During the SOT‐driven switching process, an asymmetrically manipulated state is observed. Current pulses with the same amplitude but opposite directions induce different magnetization states. Magneto–optical Kerr measurements reveal that this is due to the coexistence of stable and metastable antiferromagnetic domains in the AFM. Exploiting the asymmetric properties of these FM/AFM structures, five spin logic gates, namely AND, OR, NOR, NAND, and NOT, are realized in a single cell via SOT. This study provides an insight into the special ability of SOT on AFMs and also paves an avenue to construct the logic‐in‐memory and neuromorphic computing cells based on the AFM spintronic system.